La multiterritorialización del conflicto de las hidroeléctricas: los reasentamientos como puntos de empoderamiento del movimiento de los afectados por represas - Da Rocha, Humberto José (El Colegio de México, 2016)
The Brazilian electrical sector, with a predominant hydric matrix, generates social and environmental impacts, among which stands out the compulsory displacement of local populations. The de-territorialization and re-territorialization caused by hydroelectric plants produce a process characterized by “multiterritorialization” of conflict. This paper discusses this conflict, which involves consortiums of construction companies and the Movement of People Affected by Dams (MAB), as a contesting movement. The objective is to analyze to what extent resettlements produced by the construction of hydroelectric dams and organized by MAB potentiate actions against future constructions. Combining qualitative research with quantitative data, we present the case of the Uruguay basin, in order to demonstrate that, although they represent empowerment points, the potential of resettlements must be relativized from the standpoint of a broader social process.